FROM NATIONALISM TO FASCIST EUROPEANISM Italy, the francophone world, and the empire myth. - Rota, Emanuel, 1970- (ROUTLEDGE, 2026)
This book traces the intellectual history of fascist Europeanism, examining how Italian and Francophone fascist thinkers envisioned European unity as a means of consolidating power, overcoming nationalist divisions, and resisting external threats rather than promoting peace or democracy.Readers will discover how fascist thinkers-from Mussolini and Drieu La Rochelle to Evola, Thiriart, and Romualdi-reimagined European unity as a radical alternative to liberal democracy, driven by visions of power, hierarchy, and racial identity. By exploring pivotal debates on nationalism, modernity, and empire, this book reveals the hidden ideological struggles within fascist Europeanism and their enduring legacy in today's far-right movements. Richly grounded in historical analysis and original sources, it provides a provocative new perspective on European integration as an ongoing political battleground.This book is intended for scholars, researchers, and students of modern European history, fascism, and political ideologies. It will also be of interest to those studying contemporary far-right movements and the historical roots of European integration.